Resilience as a moderator of the relationship between organizational spirituality and burnout - Silva, Pablo Marlon Medeiros da; Sousa, Juliana Carvalho de; Castro, Ahiram Brunni Cartaxo de; Silva, Arthur William Pereira da; Guimarães, Julio Cesar Ferro de (Contextus - Revista Contemporânea de Economia e Gestão, 2023)
This study aimed to analyze the moderating role of Resilience (R) in the relationship between Organizational Spirituality (OS) and Burnout Syndrome (BOS) in call center operators. The quantitative methodology of the research type included a sample of 512 and the data were collected and analyzed from the Structural Equation Modeling. The results showed a negative relationship between OS and BOS. It was also shown that the perception of perseverance and self-confidence (dimensions of resilience) significantly moderated the association between the two constructs, reducing their effects. The present study brings contributions to science by improving the Burnout measurement tool, including the Optimism dimension in the validated scale, in addition to reinforcing the moderating role of resilience.